Plasmonic sensor realized on metal-insulator-metal waveguide configuration for refractive index detection - Butt, Muhammad Ali (Photonics Letters of Poland, 2022)
In this work, a plasmonic sensor established on metal-insulator-metal waveguide configuration is proposed and numerically investigated for biosensing applications. The spectral and sensing characteristics of the device are examined via the two-dimensional finite element method. Sensitivity (Sbulk) and figure of merit (FOM) are two important parameters that are considered to determine the device performance. The Sbulk of the device is considered as a ratio between the change in resonance wavelength and change in the ambient refractive index. Whereas FOM is the ratio of Sbulk to full width at half maximum. The Sbulk and FOM offered by the device are ~825.7 nm/RIU and ~13.14, respectively. This work can provide a guideline for the realization of highly sensitive plasmonic sensing devices. Full Text: PDF References N.L. Kazanskiy, S.N. Khonina, M.A. Butt, "Plasmonic sensors based on Metal-insulator-metal waveguides for refractive index sensing applications: A brief review", Physica E: Low-dimensional systems and Nanostructures 117, 113798 (2020). CrossRef D. Xiang, W. Li, "MIM plasmonic waveguide splitter with tooth-shaped structures", Journal of Modern Optics 61, 222-226 (2014). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "Ultra-short lossless plasmonic power splitter design based on metal–insulator–metal waveguide", Laser Physics 30, 016201 (2020). CrossRef J. Park, S. Lee, B. Lee, "Polarization Singularities in the Metal-Insulator-Metal Surface Plasmon Polariton Waveguide", IEEE Journal of Quantum Electronics 46, 1577-1581 (2010). CrossRef M. T. Hill, M. Marell, E. S. P. Leong, B. Smalbrugge, Y. Zhu, M. Sun, P. J. V. Veldhoven, E. J. Geluk, F. Karouta, Y-S. Oei, R. Notzel, C-Z. Ning, M. K. Smit, "Lasing in metal-insulator-metal sub-wavelength plasmonic waveguides", Optics Express 17, 11107-11112 (2009). CrossRef A. Udupi, S. K. Madhava, "Plasmonic Coupler and Multiplexer/Demultiplexer Based on Nano-Groove-Arrays", Plasmonics 16, 1685-1692 (2021). CrossRef Y-F. C. Chau, C-T. C. Chao, H-P. Chiang, "Ultra-broad bandgap metal-insulator-metal waveguide filter with symmetrical stubs and defects", Results in Physics 17, 103116 (2020). CrossRef H. Bahri, S. Mouetsi, A. Hocini, H.B. Salah, "A high sensitive sensor using MIM waveguide coupled with a rectangular cavity with Fano resonance", Optical and Quantum Electronics 53, 332 (2021). CrossRef S.N. Khonina, N.L. Kazanskiy, M.A. Butt, A. Kazmierczak, R. Piramidowicz, "Plasmonic sensor based on metal-insulator-metal waveguide square ring cavity filled with functional material for the detection of CO2 gas", Optics Express 29, 16584 (2021). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "Plasmonics: A Necessity in the Field of Sensing-A Review (Invited)", Fiber and Integrated Optics 40, 14-47 (2021). CrossRef M.A. Butt, A. Kazmierczak, N.L. Kazanskiy, S.N. Khonina, "Metal-Insulator-Metal Waveguide-Based Racetrack Integrated Circular Cavity for Refractive Index Sensing Application", Electronics 10, 1419 (2021). CrossRef N.L. Kazanskiy, S.N. Khonina, M.A. Butt, A. Kazmierczak, R. Piramidowicz, "A Numerical Investigation of a Plasmonic Sensor Based on a Metal-Insulator-Metal Waveguide for Simultaneous Detection of Biological Analytes and Ambient Temperature", Nanomaterials 11, 2551 (2021). CrossRef I. Tathfif, A.A. Yaseer, K.S. Rashid, R.H. Sagor, "Metal-insulator-metal waveguide-based optical pressure sensor embedded with arrays of silver nanorods", Optics Express 29, 32365-32376 (2021). CrossRef P.D. Sia, "Overview of Drude-Lorentz type models and their applications", Nanoscale Syst. Math. Model. Theory Appl. 3, 1-13 (2014) CrossRef M.A. Butt, N.L. Kazanskiy, "Nanoblocks embedded in L-shaped nanocavity of a plasmonic sensor for best sensor performance", Optica Applicata LI, 109-120 (2021). CrossRef S. Khani, M. Hayati, "An ultra-high sensitive plasmonic refractive index sensor using an elliptical resonator and MIM waveguide", Superlattices and Microstructures 156, 106970 (2021). CrossRef F. Chen, J. Li, "Refractive index and temperature sensing based on defect resonator coupled with a MIM waveguide", Modern Physics Letters B 33, 1950017 (2019). CrossRef M. Rahmatiyar, M. Danaie, M. Afsahi, "Employment of cascaded coupled resonators for resolution enhancement in plasmonic refractive index sensors", Optical and Quantum Electronics 52, 153 (2020). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "A multichannel metallic dual nano-wall square split-ring resonator: design analysis and applications", Laser Physics Letters 16, 126201 (2019). CrossRef